Thailand 4.0 and E-Readiness in ASEAN - Rotchanakitumnuai, Siriluck (NIDA Business Journal, 2023)
Thailand has set its strategic direction to lead Thailand 4.0. Electronic Readiness (E-Readiness) is one of the readiness factors to achieve Thailand 4.0 strategic goals. The objective of this paper is to assess E-Readiness of Thailand when compared to other ASEAN countries. The analysis shows that Thailand is ranked in a lower position than Singapore, Malaysia, and Brunei in the Electronic Government Development Index (EGDI) and ICT Development Index (IDI) assessment. For the World Digital Competitiveness Index (WDCI), Thailand is assessed at a lower level of E-Readiness than Singapore and Malaysia. The results demonstrate that Thailand has to close its weaknesses by enhancing the development of information and communication technology (ICT) infrastructure, online service quality, and digital expertise personnel. In addition, the incessant support of government and related stakeholders is essential so that utilization of ICT can be expanded and generate more valuable benefits to Thai society and economic development like Singapore’s.